Role of Sialic Acids in Central Nervous System Immune Response - Karolina Narejko; Martyna Niemczuk; Agata Urbaniak; Sylwia Koziej; Piotr Jakub Depta; Adrianna Jasiuk; Mateusz Wiekiera (Quality in Sport)
Sialic acids (Sia) are a structurally diverse family of nine-carbon sugars that play a crucial role in cell–cell communication, immune modulation, and neurodevelopment. Their unique ability to form homo- and oligo-polymers, along with a variety of linkages and chemical modifications, contributes to the complexity of glycosylation patterns on cell surfaces. Particularly enriched in the Central Nervous System (CNS), polysialic acids are involved in processes such as synaptogenesis, neuroplasticity, and modulation of neurotransmitter activity. This study explores the biosynthesis, recycling, and functional roles of Sia in the CNS, emphasizing their involvement in immune regulation via SIGLEC receptors and complement system modulation. It also addresses the pathological implications of Sia mimicry by pathogens such as Neisseria meningitidis and E. coli, which exploit sialylation to evade immune responses.